ON THE SPECIFICITY OF SEROLOGICAL REACTIONS WITH SIMPLE CHEMICAL COMPOUNDS (INHIBITION REACTIONS) - Landsteiner, K. (The Rockefeller University Press, 1931)
Experiments are described which confirm the result that the specificity of inhibitory reactions involving substituted aromatic acids is decidedly influenced by the position of the substituent. When antigens with specific groups of very simple constitution are used for the tests, inhibiting effects are obtained also with substances distantly related to those determining the reactivity of the antigens. On the other hand, if antigens are built up from protein and chemical compounds of somewhat higher complexity, the specificity of the inhibition reactions with synthetic crystallized substances is of the same order as that of the usual serum reactions; in other words, it is possible to distinguish such compounds by serological tests as readily as proteins can be differentiated with the aid of precipitating sera.